Relationships of Astragalus L. in section Sesamei based on morphological criteria and molecular markers (Bangladesh Journal of Plant Taxonomy, 2014)
The relationships among five species and two varieties of Astragalus L. in the section Sesamei (Fabaceae) from Egypt and Saudi Arabia have been reassessed based on morphological variation and molecular polymorphism as revealed by RAPD and ISSR fingerprinting. The analysis of morphological variation delimited the examined taxa into two groups; one comprising samples representing A. sinaicus, A. asterias and A. schimperi, and the other is comprised of two samples of A. stella and six samples representing A. tribuloides. The grouping of A. asterias and A. schimperi based on morphological criteria indicates affinities between them that were not reflected in their previous treatments. Both morphological criteria and molecular markers indicated considerable distance between the samples of A. stella and A. tribuloides. The multiform nature of A. tribuloides is confirmed as A. tribuloides var. mareoticus is clearly differentiated from the type A. tribuloides and A. tribuloides var. minutus.DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19250Bangladesh J. Plant Taxon. 21(1): 1-12, 2014 (June)